Geografia e a Educação Ambiental na escola: desenvolvendo a consciência ambiental - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This article has the general objective of identifying the contribution of environmental education through the teaching of geography to basic education students and for the construction of a sustainable environmental awareness. As a specific objective to analyze the cross-cutting themes suggested by the BNCC to be developed together with the students and what skills students should develop throughout basic education related to the environment. The methodology used was based on bibliographic sources, specific legislation on educational processes through the qualitative method to meet the proposed objective. About geography and environmental education in the light of the Law of Guidelines and Base of Education nº 9394, of the National Curriculum Parameters and of the Common National Base and of the transversality, they were the base of this work. It was found that the national legislation was built from several international conferences that pointed to the need for environmental preservation. And, it was also contacted that the school
Geography and Environmental Education at School: Developing Environmental Awareness
Keywords: Geografia; Educação Ambiental; Conciência Ambiental; Geography; Environmental Education; Environmental Awareness; CIENCIAS HUMANAS